Effects of moisture content on pumpkin crackers in different packages - Rachtanapun P. (2014)
The effect of moisture content on shelf life of pumpkin crackers in different packages (HDPE, OPP, PVDC and metallized Al pouches) was investigated. Shelf life of food products can be determined by setting sensory test. However, it is costly for determining some long shelf life products, which last for years. Therefore, using model to predict their shelf life is more useful. Samples were placed in different percentage relative humidity to study their moisture absorption behavior. The sorption isotherm curve was used to determine (Mc). Next, the water vapor transmission rate (WVTR) of the pouches was measured. Finally, the models (constant, linear, middle point, log and GAB model) were taken for shelf life prediction. The most suitable model for pumpkin crackers is middle point model because the different between shelf life of pumpkin crackers in HDPE (pumpkin crackers in other pouches have their shelf life longer than 2 months) from sensory test and shelf life from this model is only -8.70% differently. Thus, the shelf life model is very useful and convenient for food companies to predict the shelf life of their products in a short time.